The implications of the surprising existence of a large, massive CO disk in a distant protocluster - Dannerbauer, H.; Lehnert, M.D.; Emonts, B.; Ziegler, B.; Altieri, B.; De Breuck, C.; Hatch, N.; Kodama, T.; Koyama, Y.; Kurk, J.D.; Matiz, T.; Miley, G.; et al. (EDP Sciences, 2017)
It is not yet known if the properties of molecular gas in distant protocluster galaxies are significantly affected by their environment as galaxies are in local clusters. Through a deep, 64 h of effective on-source integration with the Australian Telescope Compact Array (ATCA), we discovered a massive, Mmol = 2.0 ± 0.2× 1011 M⊙, extended, ~40 kpc, CO(1–0)-emitting disk in the protocluster surrounding the radio galaxy, MRC 1138−262. The galaxy, at zCO = 2.1478, is a clumpy, massive disk galaxy, M∗ ~ 5 × 1011 M⊙, which lies 250 kpc in projection from MRC 1138−262 and is a known Hα emitter, named HAE229. This source has a molecular gas fraction of ~30%. The CO emission has a kinematic gradient along its major axis, centered on the highest surface brightness rest-frame optical emission, consistent with HAE229 being a rotating disk. Surprisingly, a significant fraction of the CO emission lies outside of the UV/optical emission. In spite of this, HAE229 follows the same relation between star-formation rate and molecular gas mass as normal field galaxies. HAE229 is the first CO (1–0) detection of an ordinary, star-forming galaxy in a protocluster. We compare a sample of cluster members at z > 0.4 thatare detected in low-order CO transitions, with a similar sample of sources drawn from the field. We confirm findings that the CO-luminosity and full-width at half maximum are correlated in starbursts and show that this relation is valid for normal high-z galaxies as well as for those in overdensities. We do not find a clear dichotomy in the integrated Schmidt-Kennicutt relation for protocluster and field galaxies. Our results suggest that environment does not have an impact on the “star-formation efficiency” or the molecular gas content of high-redshift galaxies. Not finding any environmental dependence in these characteristics, especially for such an extended CO disk, suggests that environmentally-specific processes such as ram pressure stripping do not operate efficiently in (proto)clusters.